Pollination ecology of Steveniella satyrioides (Spreng.) Schltr. (Orchidaceae) in Ayan natural landmark (the Crimea) - Fateryga, A.V.; Ivanov, S.P.; Fateryga, V.V. (Український ботанічний журнал, 2013)
The nectarless orchid, Steveniella satyrioides (Spreng.) Schltr., occurs in the mountain part of the Crimean Peninsula; it is known from 26 localities 10 of which were found during the last 50 years. Pollination ecology of the species was studied in Ayan Natural Landmark (Simferopol District). From 1 to 55 individuals of this species flowered here in different years; one year there was no flowering plants. The pollination rate of S. satyrioides varies from 16 % to 79 % and positively correlates with the density of specialized pollinators — females of diplopterous wasps of genera Vespula Thomson, 1869, and Dolichovespula Rohwer, 1916. A probable mechanism of attraction of wasps by flowers of S. satyrioides and its evolution are discussed.